(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The aim of present study was to study the impact of Sense of Coherence and Emotional Intelligence upon Managerial Effectiveness. For the purpose of the study a sample of 300 middle level managers was collected. Orientation to Life Questionnaire, Emotional Intelligence Scale and Managerial Effectiveness Scale were Used. Data was analysed in terms of Mean, SDs and 2 Way ANOVA. The results revealed that both Sense of Coherence and Emotional Intelligence have significant impact over Managerial Effectiveness.